2021
DOI: 10.1007/s00259-021-05626-3
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in the differentiation of follicular lymphoma from diffuse large B-cell lymphoma with radiomic [18F]FDG PET/CT features

Abstract: M. (2022). Machine learning in the differentiation of follicular lymphoma from diffuse large B-cell lymphoma with radiomic [F-18]FDG PET/CT features. European Journal of Nuclear Medicine and Molecular Imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
(71 reference statements)
0
10
1
Order By: Relevance
“…[23,24] Meanwhile, it is found that the radiomics based on PET-CT has a certain application value in the diagnosis of lymphoma subtypes, and it could preliminarily distinguish FL from DLBCL. [25] What surprised us is that radiomics features in our study didn't show a satisfactory result, with the AUC of 0.666, and sensitivity, speci city, accuracy of 74.1%, 55.7%, 59.7%, respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…[23,24] Meanwhile, it is found that the radiomics based on PET-CT has a certain application value in the diagnosis of lymphoma subtypes, and it could preliminarily distinguish FL from DLBCL. [25] What surprised us is that radiomics features in our study didn't show a satisfactory result, with the AUC of 0.666, and sensitivity, speci city, accuracy of 74.1%, 55.7%, 59.7%, respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…A total of 24 articles on lymphomas were included in this review [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ], 13 of which studying diffuse large B-cell lymphoma (including 2 studies on gastro-intestinal lymphoma), 3 on follicular lymphoma, 3 on Hodgkin’s lymphoma, 2 on mantle cell lymphoma and 3 on other sub-types of lymphoma. 18F-FDG was the only tracer employed and all studies built radiomic models on baseline, pre-treatment PET images, often including clinical parameters and international prognostic indices.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies evaluated the role of PET radiomics and AI analysis in blood malignancies [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ]. Lymphoma radiomics on 18F-FDG PET/CT was more often assessed on patients with DLBCL, in retrospective cohorts and for prognostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Lippi et al related good performance of ML to discriminate different types of lymphomas from each other, especially HL, but in a small population of patients (11). Recently, de Jesus et al showed very promising results to differentiate follicular lymphoma and DLBCL using radiomics and ML classifier in a population of 120 patients, which could have important clinical use when monitoring patients for aggressive transformation (14). Their best performing model showed an AUC of 0.86 significantly higher than the performance of the SUVmaxbased model (AUC 0.79).…”
Section: Discussionmentioning
confidence: 99%
“…The development of artificial intelligence and machine learning (ML) combined with radiomics has gained popularity in different medical imaging tasks, including lesion identification and characterization. In lymphoma, some studies showed the potential of [ 18 F]FDG PET/CT radiomics to differentiate lymphoma from other types of cancers and to differentiate different types of lymphoma (10)(11)(12)(13)(14). To the best of our knowledge, no study has yet explored the use of 18 F-FDG PET/CT radiomics to characterize sarcoidosis lesions, except one for the diagnosis of cardiac involvement (15).…”
Section: Introductionmentioning
confidence: 99%